Orthopedic physical examination tests an evidence-based approach - Cook, Chad; Hegedus, Eric J. (Pearson Education, 2013)
This is the field's most comprehensive evidence-based guide to clinical tests for orthopedic physical examination. This 2nd edition presents complete explanations and photography visualizing all commonly used physical exam tests for all body regions, including both neurological screening tools and conventional tests. The quality of research supporting each test is assessed using the QUADAS quality instrument, which analyzes the extent to which bias may have influenced diagnostic values. Diagnostic values are reported wherever they exist, and summary "Utility" scores are provided for each test based on the authors' interpretation of the research and their use of the tests in clinical practice. This edition adds 200 new tests, presents valuable clusters of tests, and contains two entirely new chapters: one on visceral assessment and medical screening, and another on temporomandibular examination.